Bee diversity in Angola and community change along an altitudinal gradient at Serra da Chela (Bruco) - Figueira Fernandes Elizalde, Sara Raquel (Department of Biological Sciences, 2020)
Insects, including wild bees (Hymenoptera: Anthophila) are exceptional model organisms to assess the effect of climate variation on species richness along altitudinal gradients. Climate variables and weather conditions are of extreme importance for insects particularly since their capacity of body temperature regulation is determined by the ambient temperature. Additionally, bee diversity has proven to be strongly related to the availability of host plants, determinant factors for their presence or absence and both of which are limited at higher altitudes. Therefore, the study of wild bee diversity at various altitudes in the tropics could provide information on possible responses of bee species and communities to climate variations, important to estimate effects of climate change on an important ecosystem service such as pollination. Bees being ecologically important insects with close links to plants, high richness and abundance are well-suited as terrestrial habitat bioindicators. The group is sensitive to environmental disturbances relies upon local plant communities and comprises an assemblage of species with varying social structure, nesting guilds and other life history traits. Additionally, bees are likely more susceptible to negative effects of small effective population size. The life history traits determine the individual and community response to environmental changes. Records from the literature revealed a collector and seasonal bias, with greater effort applied around big cities or specific collecting locations and mainly in the wet season. A preliminary checklist of bees of Angola was created and comprises 209 bee species from 47 genera and five families, but a major proportion of the country's area remains to be surveyed. A national inventory of Angolan bees is proposed, making use of standardized methods and sampling either one quarter degree cell or half degree cells, ideally in both dry and rainy seasons. Wild bee communities were sampled along an altitudinal gradient (760-1651 m.a.s.l) in the biodiversity rich and critically endangered Angolan escarpment. Pan traps, malaise traps and sweep netting were used at twelve sampling points, with an average of 70 m difference in altitude between points. Sweep netting proved to be the most efficient technique. Overall, 845 individuals were collected, representing 51 identified species, 34 genera and five bee families. Contrary to the trends observed in other studies in the tropics, a consistent increase in bee diversity (carried out at genera level) with increasing altitude, from the lower altitude (H'=2,14) to the higher altitude of the gradient (H'=2,26) was found. In addition, community structure differed along the gradient, with distinctive communities in low elevation sites being dominated by Braunsapis, Ceratina, Hypotrigona and Anthidiellum, and high elevation sites the distinctive communities were dominated by Amegilla, Macrogalea, Patellapis and Xylocopa. This result might be consistent with findings from studies of other taxa that attribute to the Angolan escarpment an importance as a centre of endemism and speciation. The results from this study are possibly explained by a combination of factors where the exceptional geomorphology and landscape shape the (direct) influence of environmental variables such as temperature and precipitation on the vegetation communities along the gradient therefore (indirectly) affecting bee community assemblages, particularly for the more specialized bee genera and species. Limited research has been done on the variation of bee body size along altitudinal gradients, but the few studies that have been carried out indicate that future changes (warming) in climatic conditions will most probably alter bees body size (by reduction), consequently affecting their thermoregulatory capacity and, at a larger scale, the overall patterns of community assembly. Along the tropical altitudinal gradient of this study, bee body size was found to increase with altitude by 58% (mean length at lower altitude = 5.06mm against mean = 7.99mm at higher altitude elevation sites) at the community level but also at the intra-specific level, with Macrogalea candida increasing 4% in size between the lower altitude and summit of the transect (mean length at lower altitude = 8.76mm against mean = 9.12mm at higher altitude elevation sites), suggesting that the fairly small temperature gradient along the transect was sufficient to select for body size – either directly, but more likely through multiple avenues, including indirect effects such as changes in rainfall, plant community composition and plant phenology. This result constitutes, to my best knowledge, the first demonstration of Bergmann's rule applicability at different levels of biotic organization of bee communities in the tropical region. Effective conservation planning is highly dependent on robust, spatially explicit biodiversity data. The generation of comprehensive insect profiles through long term monitoring studies at the national level can identify areas with high species turnover and endemism – patterns that could be missed if only vertebrate data were considered. In under-developed countries like Angola, where a poorly documented but highly rich biodiversity is severely threatened by unregulated land use, and research is hampered by financial constraints and lack of human resources, the combined use of indicator taxa for both terrestrial (bees) and freshwater (Odonata) environments might be a reasonable surrogate for total biodiversity status assessments. The results from this study highlight the need for long term monitoring to efficiently assess bee diversity, especially in critically endangered landscapes where anthropogenic pressures are high.